Kajian Mengenai Tukar Guling Tanah Bengkok Guna Pendirian Pabrik - Dwi Yuli Kusumaningtyas; Mohammad Fateh (Manabia: Journal of Constitutional Law, 2022)
Crooked land is land owned by the village which should be used for the benefit of the village and community. But, what if the crooked land is exchanged for other land to the private sector for the establishment of a factory? With the case there had been pros cons among the village community, so that village had to handle the situation with a solution that could relieve everyone. In this study, the author present the formulation of the problem including how the practice of swapping is carried out according to Permendagri Number 1 0f 2016 and how the impact of this event is seen from the benefit of the maslahah mursalah. This research uses empirical normative methods with qualitative research and is in the form of field research. The results of this research are the implementation of land swaps according to Permendagri number 1 of 2016 and the results of the analysis of the swap events taking into account the value of the benefits obtained based on the maslahah mursalah.